Cam Jansen and the birthday mystery - Adler, David A.; Natti, Susanna (New York : Puffin, 2002)
When Cam's grandparents are robbed on their way to her parents' surprise birthday party, Cam uses her photographic memory to solve the mystery.
3.4
3-6
Keywords: Birthdays -- Fiction; Grandparents -- Fiction; Mystery and detective stories; Birthdays -- Fiction; Grandparents -- Fiction; Mystery fiction